The Ba'th and Syria, 1947-1982: By Robert W. Olson. The Evolution of Ideology, Party, and State from the French Mandate to the Era of Hafiz al-Asad (Princeton, New Jersey: The Kingston Press, Inc., 1982), xx - 235 pp. (American Journal of Islam and Society, 1985)
As Professor Olson explains in his preface, this book is intended to be "an intermediate essay" - something that combines the two opposite approaches that he has found to be inadequate for most students. He identifies these two approaches as, on the one hand, specialized studies written by social scientists emphasizing theoretical concepts relating to development and underdevelopment and suitable to advanced students and, on the other hand, general textbooks on the history of the entire Middle East since before the rise of Islam. In effect, he is proposing to write a general account of contemporary Syria, particularly on the rise of the Ba'th Party and the history of the country under Ba'thist rule. Not only is he right about the need for such surveys, but he has also done quite a good job with this one. While its usefulness could have been enhanced by the availability of an inexpensive paperback edition. this book should serve the purpose of courses on twentieth century Middle Eastern history quite well. Portions of the book could also be used in various social science courses in conjunction with works of a more theoretical nature. Professor Olson's book is like most surveys - "intermediate" or more general - in not being based primarily on his own original research. He uses some primary materials, like writings of Michael Aflaq, but in the main this book is a synthesis of books and articles by such people as Tabitha Petran, Patrick Seale, Gordon Torrey, Raymond Hinnebusch, Malcolm Kerr, and Nikolaos Van Dam. The author was quite conscientious about giving credit to all of these secondary works, as indicated by his 22 pages of footnotes for 188 pages of text; this, together with an excellent lengthy bibliography, provides a valuable guide for students and others who want to pursue particular matters in depth. The author provides what, in many ways, is a favorable picture of the al-Asad regime, particularly during its early years. The regime is said, despite the predominance of the Alawi minority in it, to have widespread support not just among minorities but throughout the rural areas (even extending to Sunnis, including devout ones), where its achievements have been considerable, and to have been in the process of further ...